Effect of during of tapering on anaerobic power and capacity in road cyclists - Fortes, L. S.; Costa, B. D. V.; Paes, S. T.; Perez, A. J.; Diefenthaeler, F. (Science & Sports, 2020)
The linear tapering method duration can be determinant for sport performance. Objective: The objective of this study was to analyze the effect of linear tapering duration method on anaerobic power and capacity in road cyclists. Materials and methods: Seventeen male road cyclists,aged between 18 and 30 years were randomly selected within the study criteria. Participants performed 16 weeks of training,adopt ing the undulating periodization with weekly variation of the training load. The tapering phase lasted 4 weeks,using the linear tapering method,reducing only the training volume: 85% in the first,70% in the second,55% in the third and 40% in the fourth week. The Wingate test was used to evaluate anaerobic power and capacity. Wingate was performed by the cyclists before the start of the season,at the end of the last week of each mesocycle (Preparatory I,Specific I and Specific II) and at the end of each week in the tapering phase. Results: The results revealed a time effect for anaerobic power (P < 0.01) and capacity (P < 0.01), with an increase after the preparatory phase I compared to pre-experimental (P = 0.01),maintenance until phase specific II (P = 0.01),maintenance in the third week of tapering (P > 0.05),finishing with attenuation in the fourth week of tapering (P = 0.01). Conclusion: It was concluded that 2 weeks of tapering was enough to improve the anaerobic power and capacity in road cyclists.